2019
DOI: 10.1080/21691401.2019.1594000
|View full text |Cite|
|
Sign up to set email alerts
|

Propofol inhibits proliferation and epithelial-mesenchymal transition of MCF-7 cells by suppressing miR-21 expression

Abstract: Breast cancer is a common malignant tumor with a high incidence of recurrence and metastasis. It has been reported that propofol has certain anti-breast cancer effects, but the intrinsic molecular mechanism remains unclear. This study investigated the effect of propofol on breast cancer MCF-7 cells and its possible regulatory mechanisms. MCF-7 cells were treated by propofol, and then the effects of propofol on cell growth and epithelial-mesenchymal transition (EMT) were studied. We subsequently testified wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…Specifically, the following findings from cell culture models showed that miR-15a-5p [53], MicroRNA-582-5p [54] and miR-34a [55] were involved in propofol-induced neuron and astrocyte death, respectively; miR-21 was involved in propofol-induced inhibition of proliferation and epithelial-mesenchymal transition in breast cancer cells [56]; miR-495 was involved in propofol-induced inhibition of proliferation and metastasis in JEG-3 choriocarcinoma cells [57]. In this study, propofol treatment decreased cell migration followed by miR-34a and E-cadherin upregulation in the PANC-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the following findings from cell culture models showed that miR-15a-5p [53], MicroRNA-582-5p [54] and miR-34a [55] were involved in propofol-induced neuron and astrocyte death, respectively; miR-21 was involved in propofol-induced inhibition of proliferation and epithelial-mesenchymal transition in breast cancer cells [56]; miR-495 was involved in propofol-induced inhibition of proliferation and metastasis in JEG-3 choriocarcinoma cells [57]. In this study, propofol treatment decreased cell migration followed by miR-34a and E-cadherin upregulation in the PANC-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…We discovered the involvement of miR-21, which is a major player involved in tumor initiation, progression and metastasis of various types of cancers (Frankel et al, 2008;Zhu et al, 2008;Qi et al, 2009;Tian et al, 2019), including CRC (Yang et al, 2017), and considered as a representative oncogenic miRNA. Interestingly, EMT can be inhibited by down-regulating miR-21 expression in breast cancer cell (Du et al, 2019). These observations are consistent with our findings that ALKBH4 suppresses the expression of miR-21 by decreasing H3K4me3 modification in the promoter region and eventually inhibits EMT in CRC cells.…”
Section: Discussionsupporting
confidence: 92%
“…of cancer cells is overwhelming to ignore 8,9 . Against breast cancer cells, propofol is particularly effective with demonstrated role in preventing proliferation 10 , inducing apoptosis 11 and reducing metastasis 12 .…”
mentioning
confidence: 99%